Enhancing Automation and Data Acquisition Learning Through Web Virtual Reality: Utilization and Practicality - Syarif, Muhammad Ilyas; Muhammad Yahya; Abdul Muis Mappalotteng (International Journal of Education, Vocational and Social Science, 2024)
A good learning process must contain interactive, fun, challenging, motivate and provide more space for students to be able to develop creativity and independence, according to the talents and interests of students. Vocational High School prioritizes practicum over theory. Need considered in the selection of media, namely learning objectives, effective, easy to obtain, students, usage, cost, and quality. One of the developments of learning media that is currently still the new one is learning media using Web Virtual Reality. Web Virtual Reality can be built using the help of Vuforia and Unity 3D software. The final result is an interactive learning media with Web Virtual Reality. The results of the analysis of the validity of the developed learning media obtained an average value of 3.21 with the category “Valid”. The average practicality of Web Virtual Reality learning media is “very practical” category.